The Influence of Communication Competence, Emotional Intelligence, and Organizational Culture on Employee Performance at the Indonesian Land Transportation Polytechnic (PTDI-STTD) - Gunawan, Ridwan; Susilastuti, Darwati; Rojali, Muhammad (Jurnal Greenation Sosial dan Politik, 2025)
This study aims to analyze the influence of communication, emotional intelligence, and organizational culture on employee performance at the Indonesian Land Transportation Polytechnic-STTD (PTDI-STTD). In the era of digital transformation and globalization, employee performance becomes a fundamental factor determining organizational success in achieving strategic goals. The research employed a quantitative descriptive design with an explanatory approach involving 105 civil servant employees as respondents selected through stratified random sampling technique. Data collection was conducted using closed questionnaires with a 1-5 Likert scale, then analyzed using SPSS with multiple linear regression techniques. The results showed that simultaneously, communication, emotional intelligence, and organizational culture significantly influence employee performance (F calculated 40.344 > F table 2.69, sig. 0.001 < 0.05). Partially, all three variables also proved to have significant effects with organizational culture showing the most dominant influence (? = 0.478), followed by emotional intelligence (? = 0.201), and communication (? = 0.134). The coefficient of determination of 0.822 indicates that 82.2% of employee performance variation can be explained by these three variables. These findings confirm the importance of an integrated approach in developing effective communication, emotional intelligence, and positive organizational culture to improve employee performance in higher education transportation institutions.